The shoulder range of motion of alternative spike/serve techniques as a potential injury predictor in volleyball - Seminati, E. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Volleyball is at the third place after Soccer and Basket within the sport activities causing injuries. Overuse and stresses during the traditional spike and serve movements, make the shoulder one of the most commonly exposed body part (Chan et al. 1993, Verhagen et al. 2004). Pain, reduced range of motion and mobility, bring often the athletes to prematurely interrupt their career. Different spike techniques are supposed to be associated to different risk damage of the shoulder joint. Here we compared two of them by also regarding the skills and fitness necessary for the athletes` performance. Methods: 21 volleyball players, from high-level National categories, performed the spike movement using a traditional and an alternative technique, (TT and AT respectively), in 3 different conditions: without jumping, jumping with and without hitting the ball. Upper limb and trunk were modelled, as multilink segment structures (Murray, 1999). 3D positions of 16 reflective markers were recorded with a 6-camera optoelectronic system (f=250Hz). Glenohumeral centre was viewed as the centre of an imaginary sphere described by the distal end of the humerus, with a radius of 200 mm. The spatial relationships between humerus and trunk (considered as a relative system, to have data independently on the investigated condition) were described on this sphere in terms of an angle of azimuth (longitude on the sphere), elevation (latitude on the sphere) and axial rotation (intra-extra rotation) of the humerus about its longitudinal axis (An et al 1991). Ball speed was measured with a high-frequency camera (200Hz). Results: Preliminary results showed that the two techniques (TT and AT) travel along two significantly different trajectories on the imaginary sphere. Maximal humerus elevation was reduced by the 15% in AT, while the azimuth angular amplitude was significantly higher for the AT, compared to the TT. Ball Speed, arm velocity and maximal arm height had higher values for the AT, in each of the three considered conditions. Discussion: We performed a quantitative 3D comparison of two different spike techniques in the volleyball game. Our results suggest that the AT could be potentially a preventive solution to the shoulder chronic pathologies, while maintaining, or even enhancing, athletes` performance.